Postglacial colonization of the Qinling Mountains: phylogeography of the swelled vent frog (Feirana quadranus). - Bin Wang (Public Library of Science (PLoS), 2012)
Background The influence of Pleistocene climatic fluctuations on intraspecific diversification in the Qinling-Daba Mountains of East Asia remains poorly investigated. We tested hypotheses concerning refugia during the last glacial maximum (LGM) in this region by examining the phylogeography of the swelled vent frog (Feirana quadranus; Dicroglossidae, Anura, Amphibia). Methodology/principal findings We obtained complete mitochondrial ND2 gene sequences of 224 individuals from 34 populations of Feirana quadranus for phylogeographic analyses. Additionally, we obtained nuclear tyrosinase gene sequences of 68 F. quadranus, one F. kangxianensis and three F. taihangnica samples to test for mitochondrial introgression among them. Phylogenetic analyses based on all genes revealed no introgression among them. Phylogenetic analyses based on ND2 datasets revealed that F. quadranus was comprised of six lineages which were separated by deep valleys; the sole exception is that the Main Qinling and Micang-Western Qinling lineages overlap in distribution. Analyses of population structure indicated restricted gene flow among lineages. Coalescent simulations and divergence dating indicated that the basal diversification within F. quadranus may be associated with the dramatic uplifts of the Tibetan Plateau during the Pliocene. Coalescent simulations indicated that Wuling, Daba, and Western Qinling-Micang-Longmen Mountains were refugia for F. quadranus during the LGM. Demographic analyses indicated that the Daba lineage experienced population size increase prior to the LGM but the Main Qinling and the Micang-Western Qinling lineages expanded in population size and range after the LGM, and the other lineages almost have stable population size or slight slow population size decline. Conclusions/significance The Qinling-Daba Mountains hosted three refugia for F. quadranus during the LGM. Populations that originated in the Daba Mountains colonized the Main Qinling Mountains after the LGM. Recent sharp expansion of the Micang-Western Qinling and Main Qinling lineages probably contribute to their present-day secondary contact.